2014
DOI: 10.1097/nnr.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden and Satisfaction in Families of Individuals With Schizophrenia

Abstract: Caring for family members with schizophrenia is burdensome but can also be a source of satisfaction. Correlates of caregiver burden appeared to be somewhat distinct from those of caregiver satisfaction. Further research on negative and positive aspects of caregiving is warranted to broaden the understanding of caregiving experiences and design therapeutic interventions to mitigate caregiver burden and enhance the sense of satisfaction with caregiving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 23 publications
7
43
0
3
Order By: Relevance
“…Although numerous studies have yielded equivocal results regarding the association between family burden and age [14, 25, 26], gender [2729], and kinship [21, 30] of patients and caregivers, a growing body of research congruously indicated that family burden decreases with increasing socioeconomic status [14, 31, 32]. …”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have yielded equivocal results regarding the association between family burden and age [14, 25, 26], gender [2729], and kinship [21, 30] of patients and caregivers, a growing body of research congruously indicated that family burden decreases with increasing socioeconomic status [14, 31, 32]. …”
Section: Introductionmentioning
confidence: 99%
“…Third, given our study parameters focusing on subjective burden, we were not able to include other positive aspects of caregiving. However, we recognize that caring for a family member with schizophrenia can be rewarding, as reported in various studies (Bauer, Koepke, Sterzinger, & Spiessl, 2012; Heru, 2000; Hsiao & Tsai, 2014; Veltman, Cameron, & Stewart, 2002; Zauszniewski, Bekhet, & Suresky, 2010). Consequently, further research examining caregiving should consider incorporating a multidimensional perspective that allows for different components of the caregiving experience, including benefits and strengths.…”
Section: Discussionmentioning
confidence: 89%
“…The CASI is a 30-item scale measuring satisfaction of caregivers in three domains: satisfaction with the persons they are caring for (10 items), satisfaction with being a caregiver (12 items), and satisfaction with the interpersonal dynamics between caregivers and the persons they are caring for (eight items). Hsiao and Tsai (2014) reported a coefficient alpha of .94, which is likely to be interpreted by readers as indicating that the summed item scores of caregivers' satisfaction are "reliable. "…”
Section: Fa Reliability Coefficientsmentioning
confidence: 97%
“…It would have been interesting if Hsiao and Tsai (2014) would have taken an FA approach in their study. They could have investigated whether the items meet the assumptions underlying coefficient alpha.…”
Section: Fa Reliability Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation